Toxilogical screening of some Nigerian wild legumes - Kadiri, Mukaila (1996)
Toxilogical screening was carried out on seeds of five wild leguminous plants: Delonix regia, Cassia tora, Sesbania sesban, Crotalaria naragutensis and Tamarindus indica. The animals used in the toxicological screening were mice and rats. The leguminoous seeds have high protein contents which range between 21.1 % for S. sesban and 47.7% for C. naragutensis, while the mineral elements detected in appreciable quantities were calcium, magnesium, potassium, icon, cooper, zinc, phosphorus and sodium. Oxalate contents were very low and they range between 0.03% for S. sesban and 0.09% for C. tora. Acute toxicity test for 12 days using mice and rats given water extracts of the five legumes through the oral and intraperitoneal routes produced no visible negative effects. The treatment instead resulted in increases in fresh weights of the rats and mice when compared with the control aniínals that were fed or injected distilled water. There were also increases in blood sera protein and sugar contents of rats injected intraperitoneally with concentrated water extracts. Similar results were obtained in the prolonged toxicity screening.